Interactions between the Aryldiazonium Cations and Graphene Oxide: A DFT Study - Avni Berisha (Journal of Chemistry)
Understanding the grafting behavior of the aryldiazonium cations is of fundamental and also of practical importance for the vast number of applications that involve the use of modified graphene oxide (from simple adsorption process to electronic and photovoltaic applications). In this work, the mechanism of the adsorption and grafting of diazonium cations on the graphene oxide surface was investigated by the use of density functional theory. Two types of aryldiazonium cations, one bearing only phenyl ring and the other nitrophenyl, were selected as adsorbates/grafted moiety. By evaluating the adsorption energies at 7 different positions onto the graphene oxide both in the gaseous and solvent phase (using COSMO approach), the most probable adsorption sites were found. Moreover, the most stable adsorption sites were used to calculate and plot NCI (noncovalent interactions). The obtained results are important as they not only give molecular insights regarding the nature of the interaction and its dependence on the adsorption site of the graphene oxide surface but also on the activation energy for such a grafting reaction to take place, providing a mechanistic aspect to understand these grafting reactions.